Correlations between Personality Traits, Patient-Reported Outcome, and Chronic Prostatitis Symptoms in Men with Different Premature Ejaculation Syndromes. (8th April 2022) - Gao, Jingjing; Gao, Rui; Liu, Xi; Li, Chengfu; Gao, Pan; Du, Junhua; Zhang, Xiansheng
Abstract : Although the personality traits (PT), patient-reported outcome (PRO), and chronic prostatitis (CP) symptoms in premature ejaculation (PE) have been evaluated, there was no study to assess their correlations in men with different PE syndromes. The purpose of this study was to assess the correlations between the PT, PRO, and CP symptoms in men with different PE syndromes. Between January 2019 and January 2021, a cross-sectional field study was conducted in our andrology clinic. Men with the complaints of PE were divided into lifelong PE (LPE), acquired PE (APE), variable PE (VPE), and subjective PE (SPE). All subjects were required to complete a verbal questionnaire with the PRO, National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI), and Temperament and Character Inventory (TCI-R). Finally, 479 men with the complaints of PE and 365 without the complaints of PE were enrolled. The incidence of PE syndromes in PE complaint group was as follows: LPE 16.70%, APE 48.85%, VPE 11.27%, and SPE 23.17%. Mean ages in PE complaint group were 42.53 ± 12.25 years. In the PE complaint group, the novelty seeking (NS) scores were strongest correlated with the personal distress and quality of life (QOL) . The harm avoidance (HA) scores were strongest correlated with the severity of PE and pain syndromes . The self-transcendence (ST) scores were strongest correlated with the satisfaction with sexual intercours e and QOL . In addition, strongest association between the total scores of NIH-CPSI and the NS or ST scores was also found in the APE group. The HA scores were also strongest correlated with the total scores of NIH-CPSI in SPE. Strongest association between the total scores of NIH-CPSI and the NS/TI or ST/CI scores was also found in the APE group. The HA/TI scores were also strongest correlated with the total scores of NIH-CPSI in SPE.